Hubungan Antara Self-Efficacy Dan Kecerdasan Emosional Dengan Kemandirian Pada Remaja - Uzlifatul Jannah, Ema (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study aimed to investigate the relationship between self-efficacy and emotio-nal intelligence with teenage independence. The subjects were students of class X - XI MA Bahr Ulum Kupang Jetis Mojokerto 2012-2013 school year. Quantitative research design using a Likert scale models with self-efficacy variables of emotional intelligence. Data analysis using regression and partial. The results showed no relationship between self-efficacy and emotional intelligence with the independence of the value of F = 6.856 p = 0.002 (p <0.01), there is a relationship between self-efficacy and self-reliance with a value of t = 3.312 to p = 0.002 (p <0.01), there was no relationship between emotional intelli-gence and independence to the value t = -1.885 at p = 0.064 (p> 0,01). Price coefficients Î²o = 135.057 at SD = 19.39984; Î²1 = 0.374 and Î²2 = -0.213 with a 17.4% effective contri-bution.Keyword:Â  self efficacy â€“ emotional intelligence - self-reliance